Pengembangan Kurikulum Sekolah Bertaraf Internasional - Herry Widyastono (Jurnal Pendidikan dan Kebudayaan, 2010)
Since the government of Indonesia has launched the Decree of Republic Indonesia Number 20 year 2003 regarding The National Education System and The Government Regulation year 2005 in relation to National Education Standard, the government was implemented the schoolâ€™s piloting on international standard. However, in itsâ€™ curriculum development was not expected with the intended regulation. The expectation of the school curriculum is supposed to be the curriculum used by the country under the OECD (Organization for Economic Co-operation and Development). The intended curriculum in this matter particularly is the curriculum used by the educational concern which is reference to the Graduate Competence Standard (SKL) and the Content Standard (SI) that all enrich to with reference to the OECD member country or the curriculum used by developed countries. To enrich the curriculum can be done by two ways. First is adaptation. It means to adapt certain part of the National Education Standard with reference to the OECD member countries. Second is adoption. It means to add some certain parts of curriculum of the OECD member countries or others which is not included in the national content standard. Therefore, the graduates have qualification from both the national education system as well as from the OECD member countries.Â ABSTRAKSejak berlakunya UU Nomor 20 Tahun 2003 tentang Sistem Pendidikan Nasional dan PP Nomor 19 Tahun 2005 tentang Standar Nasional Pendidikan, Pemerintah telah menyelenggarakan rintisan sekolah bertaraf internasional (RSBI). Namun, dalam pengembangan kurikulumnya belum seperti yang diharapkan. Kurikulum yang digunakan seharusnya kurikulum yang disusun dan dilaksanakan oleh masing-masing satuan pendidikan mengacu pada Standar Kompetensi Lulusa (SKL) dan Standar Isi (SI) yang â€œdiperkayaâ€ dengan mangacu pada kurikulum salah satu negara anggota Organization for Economic Co-operation and Development (OECD) dan/atau negara maju lainnya yang mempunyai keunggulan tertentu di bidang pendidikan. â€œDiperkayaâ€ dapat dilaksanakan melalui dua cara: 1) Adaptasi, yaitu penyesuaian unsur unsurÂ tertentu yangsudah ada dalam SI/SKL dengan mengacu pada kurikulum salah satu negara anggotaÂ OECD dan/atau negara maju lainnya, dan 2) Adopsi, yaitu penambahan unsur-unsur tertentu yang belum ada dalam SI/SKL dengan mengacu pada kurikulum salah satu negara anggota OECD dan/atau negara maju lainnya. Dengan demikian, lulusannya dapat memiliki sertifikat (ijazah) dari Indonesia dan dari alah satu negara anggota OECD dan/atau negara maju lainnya.Â